Natural killer cells: From surface receptors to the cure of high‐risk leukemia (Ceppellini Lecture) - Falco, Michela (HLA, 2019)
Natural killer (NK) cells are innate immune effector cells involved in the first line of defense against viral infections and malignancies. In the last three decades, the identification of HLA class I‐specific inhibitory killer immunoglobulin‐like receptors (KIR) and of the main activating receptors has strongly improved our understanding of the mechanisms regulating NK cell functions. The increased knowledge on how NK cells discriminate healthy cells from damaged cells has made it possible to transfer basic research notions to clinical applications. Of particular relevance is the strong NK‐mediated anti‐leukemia effect in haploidentical hematopoietic stem cell transplantation to cure high‐risk leukemia.